Rustler Mountain [large type] - Yates, Maisey (Thorndike Press large print basic, 2025)
"Every year, thousands of people come through Rustler for the rodeo, historic home tours, old-fashioned candy-making demonstrations, sharpshooter shows and to see the site of the 1800s shootout in which notorious outlaw Austin Wilder was killed by Sheriff Lee Talbot. Now Millie Talbot, the sheriff's descendant, wants to bring back the town's Gold Rush Days, but she needs the current Austin Wilder's support to make her dream a reality. . . The Wilders are rumored to be as true to their last name as their ancestors. Nonetheless, Austin is agreeable to helping Millie. But he wants something in return. Austin is working to clear his family name by writing the true history of his outlaw ancestors and Millie might just hold the key. When Millie wrangles Austin into helping plan Gold Rush Days, he figures it's a chance to get to the truth of the past. . . . But when sparks start to fly between this bad boy and good girl, will either of them come out of it unscathed?"--